2018
DOI: 10.1002/stem.2854
|View full text |Cite
|
Sign up to set email alerts
|

Serine Threonine Kinase Receptor-Associated Protein Deficiency Impairs Mouse Embryonic Stem Cells Lineage Commitment Through CYP26A1-Mediated Retinoic Acid Homeostasis

Abstract: Retinoic acid (RA) signaling is essential for the differentiation of embryonic stem cells (ESCs) and vertebrate development. RA biosynthesis and metabolism are controlled by a series of enzymes, but the molecular regulators of these enzymes remain largely obscure. In this study, we investigated the functional role of the WD-domain protein STRAP (serine threonine kinase receptor-associated protein) in the pluripotency and lineage commitment of murine ESCs. We generated Strap knockout (KO) mouse ESCs and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In sum, these studies define a genome-wide AS network that STRAP regulates in a coordinated manner. We reveal the position-dependent and context-dependent effects of STRAP on splicing regulation during neuroectodermal lineage commitment, which adds another layer of complexity to the cross- 18 . The medium was changed daily.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In sum, these studies define a genome-wide AS network that STRAP regulates in a coordinated manner. We reveal the position-dependent and context-dependent effects of STRAP on splicing regulation during neuroectodermal lineage commitment, which adds another layer of complexity to the cross- 18 . The medium was changed daily.…”
Section: Discussionmentioning
confidence: 96%
“…In our previous study, we found that STRAP affects neural patterning in early Xenopus embryogenesis 18 . Given that STRAP is a conserved WD-40 domain-containing protein across species, we hypothesized that it has a functional role in AS regulation in Xenopus.…”
Section: Strap Regulates Exon Skipping During Vertebrate Evolutionmentioning
confidence: 90%
See 3 more Smart Citations